Sleep, beds, and death in ancient Egypt. Studies on the bed as a female entity - Schutz, MY (2022)
The aim of the following thesis ‘Sleep, Beds, and Death. Studies on the Bed as a Female Entity’ is to create a first overview of these pieces of furniture in the funerary context, from Predynastic times to the Roman Period—due to the constraints of this thesis, the focus was placed on the Pre- and Early-Dynastic Period and the Old Kingdom, i.e., the beginning of the bed’s occurrence in tombs, as well as the royal tombs of the New Kingdom due to its wealth of material, textual, pictorial, as well as archaeological. Moreover, these pieces of furniture were particularly examined in connection with female entities, the mother-goddesses, who are involved in the daily rebirth of the sun and, thus, the sleeper-deceased. The present work does certainly not claim to be exhaustive—such an exhaustiveness not possible in the connection with the ubiquitous beds—, but it is hoped that it can give a first, an introductory overview of this piece of furniture in the world (and worldview) of the ancient Egyptians.